Maternal Risk Factors and Morbidity Pattern of Very Low Birth Weight Infants: A NICU Based Study at Eastern Nepal - Poudel, Prakash; Budhathoki, Sunil; Shrivastava, Manoj Kumar (Journal of Nepal Paediatric Society, 2009)
Background: Preterm deliveries of babies weighing less than 1500 grams (VLBW, very low birth weight) are of major concern because of maximum perinatal morbidity and mortality found in this group. VLBW babies overload the neonatal intensive care unit (NICU) and their mortality contributes significantly to neonatal and infant mortality. Objectives: To study the common maternal risk factors associated with VLBW births. To study the morbidity and mortality patterns of VLBW babies. Methods: This was a hospital based retrospective study done in NICU of BP Koirala Institute of Health Sciences. Data were collected from medical records of VLBW babies admitted in NICU over a period of three years (13 April 2005 to 12 April 2008). Data were analyzed with SPSS 10.0 software. Results: Data of 140 VLBW babies were analyzed. Mean birth weight was 1188.9 (±212.78), 10.7% were home deliveries, 24.3% were twins, 31.4% required active resuscitation at birth and 46.4% were exposed to antenatal steroid. Common maternal risk factors associated with premature deliveries were inadequate antenatal check up (ANC) visits (95.7%), twin pregnancy (24.3%), antepartum hemorrhage (APH, 28.6%), premature rupture of membrane (23.6%), pregnancy induced hypertension (12.9%), bad obstetric history (12.9%) and maternal age less than 20 years (8.6%). Common morbidities among VLBW babies were clinical sepsis (77.1%), non physiological hyperbilirubinemia (73.6%), apnea (48.6%), shock (42.9%), hypoglycemia(39.3%), anemia (29.3%), hyaline membrane disease (HMD, 21.4%), patent ductus arteriosus (15.0%), severe hypothermia (12.1%), culture proven sepsis (15.7%), retinopathy of prematurity (5.7%), and bronchopulmonary dysplasia (3.6%). Overall survival was 54.3% and major causes of death were HMD (51.0%) and sepsis (34.7%). Median durations of hospital stay were 17.5 days for survivors and five days for expired cases. Conclusion: Increasing the coverage of ANC visits, early diagnosis and treatment of APH and pregnancy induced hypertension, discouraging the childbirth at too young age, early diagnosis and treatment of acute infections and chronic medical diseases in mothers are important measures to decrease the burden of VLBW births. Common morbidities in VLBW babies are sepsis, HMD, apnea, hyperbilirubinemia, patent ductus arteriosus, shock, anemia, hypoglycemia, hypothermia and hypocalcemia. Common causes death of VLBW babies are HMD and sepsis. Overall survival of VLBW babies in our settings is less. More numbers of well equipped NICUs and services like surfactant therapy are needed to improve survival of VLBW infants in our set up. Key words: Maternal risk factors, Morbidity, Mortality, Very low birth weight. doi: 10.3126/jnps.v29i2.2040 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.59-66